Inside the Titanic - Brewster, Hugh 1950- (Little, Brown and Company, 1997)
Text and cut-away illustrations feature the stories of real-life children who sailed aboard the Titanic on the night of its disaster in the North Atlantic
Keywords: Titanic (Steamship) / Juvenile literature; Shipwrecks / North Atlantic Ocean / Juvenile literature; Titanic (Steamship); Shipwrecks; Naufrages / Atlantique Nord / Ouvrages pour la jeunesse; North Atlantic Ocean; Young adult nonfiction; Juvenile works; Books; Literature